Signiﬁcance of scientiﬁc and technological innovation to national wealth and quality of life of rural population - Ning , Jing; Lemeschenko, Petr S. (Journal of the Belarusian State University. Economics, 2024)
This article examines the signiﬁcance of economic development in rural areas of China within the context of enhancing the overall national wealth of the country. Special attention is given to the role of scientiﬁc and technological innovation in increasing the incomes of China’s rural population, as well as the measures and achievements implemented by China to improve the lives of rural residents through scientiﬁc and technological innovation. The article also emphasises the importance of the prosperity of the agricultural population and the development of agricultural technologies in the context of enhancing China’s national wealth.